2023
DOI: 10.3389/fimmu.2023.1208631
|View full text |Cite
|
Sign up to set email alerts
|

FcγR requirements and costimulatory capacity of Urelumab, Utomilumab, and Varlilumab

Abstract: IntroductionTargeting costimulatory receptors of the tumor necrosis factor receptor (TNFR) superfamily with agonistic antibodies is a promising approach in cancer immuno therapy. It is known that their efficacy strongly depends on FcγR cross-linking.MethodsIn this study, we made use of a Jurkat-based reporter platform to analyze the influence of individual FcγRs on the costimulatory activity of the 41BB agonists, Urelumab and Utomilumab, and the CD27 agonist, Varlilumab.ResultsWe found that Urelumab (IgG4) can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…In addition, Fc N ‐glycosylation has been shown to affect the affinity of IgG for all FcγR classes (CD64, CD32 and CD16) and to C1q (Hayes et al ., 2014 ). We used a flow cytometry‐based assay to test the binding of our plant‐derived DL variants to cells expressing high levels of different human FcγRs—CD16A, the natural V176 high‐affinity variant of CD16A (C16V), CD32A, CD32B and CD64 (Leitner et al ., 2023 ). Cells not expressing human FcγR were used as a control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Fc N ‐glycosylation has been shown to affect the affinity of IgG for all FcγR classes (CD64, CD32 and CD16) and to C1q (Hayes et al ., 2014 ). We used a flow cytometry‐based assay to test the binding of our plant‐derived DL variants to cells expressing high levels of different human FcγRs—CD16A, the natural V176 high‐affinity variant of CD16A (C16V), CD32A, CD32B and CD64 (Leitner et al ., 2023 ). Cells not expressing human FcγR were used as a control.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the binding of DL variants to human FcγRs, we used a set of BW5147 lines stably expressing high levels of human FcγR—CD16A (FcγRIIIA), the natural V176 high‐affinity variant of CD16A (FcγRIIIA 176 V), CD32A (FcγRIIA), CD32B (FcγRIIB) and CD64 (FcγRI) (Leitner et al ., 2023 ). BW5147 cells not expressing human FcγR were used as a control.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we found that engagement of 4-1BB and CD27 by their natural ligands also induced potent upregulation of NF-kB and AP-1 reporter gene expression and a modest downregulation of NFAT activity. 31 We also performed some experiments with chimera harboring mICOS ectodomains lacking the dimerization motif, but due to a poor expression of these chimeric receptors their costimulatory capacity was weak. Furthermore, downregulation of NFAT activation via 4-1BB and CD27 signaling, which also occurs upon engagement of 4-1BB and CD27 with their natural ligands, was not observed with mICOS chimera lacking the dimerization motif.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry analysis was performed using constant cell volumes, flow rates, and acquisition time for all samples to detect target cell loss as described recently. 85 Cytotoxicity was measured as percentage of Annexin V-positive target cells of all target cells.…”
Section: Methodsmentioning
confidence: 99%